KARAKTERISTIK DAERAH TERHADAP BELANJA MODAL DENGAN PEMODERASI PERTUMBUHAN EKONOMI - Alfasadun Alfasadun; Pancawati Hardiningsih; Indri Nur Wakhidati (Dinamika Akuntansi Keuangan dan Perbankan, 2017)
This study aims to analyze the effect of the Original Income, the difference between the expenditure budget, and the Area of Capital expenditure with economic growth as a moderating variable. Population in this research is Regency / City of Province of Central Java counted 35 which consist of 29 regency and 6 municipality. Sample Samples selected were 35 districts / cities with census technique. Secondary data retrieval method using report from BPS in Regency / Municipality of Central Java Province. The analysis used multiple linear regression model of moderation model with the basis of interaction. The results showed that PAD has a positive effect on capital expenditure. Similarly, SiLPA has a positive effect on capital expenditure. The area has positive effect on capital expenditure. Economic Growth is a positive influence on capital expenditure. Economic growth strengthens the effect of PAD on capital expenditures. While Economic Growth is not proven to strengthen the influence of SiLPA on capital expenditure. Keywords: local original revenue, SiLPA, area, economic growth, capital expenditure